Construction and Immunogenicity of a Recombinant Pseudorabies Virus Variant With TK/gI/gE/11k/28k Deletion - Yan, Shijun; Huang, Baicheng; Bai, Xiaofei; Zhou, Ying; Guo, Linghua; Wang, Tongyan; Shan, Yihong; Wang, Yuzhou; Tan, Feifei; Tian, Kegong (Frontiers in Veterinary Science, 2022)
In China, the re-emerging pseudorabies virus (PRV) variant has caused large-scale outbreaks of pseudorabies in swine herds with classical PRV vaccine immunization since late 2011. Here, a recombinant PRV with TK/gI/gE/11k/28k deletion was constructed based on variant HN1201 strain isolated in 2012, by the bacterial artificial chromosome infectious clones. Compared with the parental virus, the recombinant PRV rHN1201TK−/gE−/gI−/11k−/28k− showed a similar virus grown curve and exhibited smaller plaques. The vaccination of rHN1201TK−/gE−/gI−/11k−/28k− could elicit an earlier and higher level of gB antibody, and the neutralizing antibodies elicited by rHN1201TK−/gE−/gI−/11k−/28k− were effective against both PRV classical and variant strains. Clinically, the body temperature of the pigs immunized with rHN1201TK−/gE−/gI−/11k−/28k− was significantly lower than that of the classical PRV vaccine immunized pigs, and the recombinant PRV could provide effective protection against the challenge with the PRV variant. These results imply that the rHN1201TK−/gE−/gI−/11k−/28k− could be a promising vaccine candidate for the prevention of the current epidemic of pseudorabies in China.